N2O selectivity in industrial NH3 oxidation on Pt gauze is determined by interaction of local flow and surface chemistry: A simulation study using mechanistic kinetics. (12th October 2022) - Haas, M.; Nien, T.; Fadic, A.; Mmbaga, J.P.; Klingenberger, M.; Born, D.; Etzold, B.J.M.; Hayes, R.E.; Votsmeier, M.
Graphical abstract: Highlights: Flow simulations of ammonia oxidation on Pt-gauzes applying mechanistic kinetics. First observation of local variation in N2 O selectivity across gauze. Upstream wires influence downstream N2 O selectivity due to flow-guiding effect. Results explain how gauze geometry influences N2 O selectivity. Simulations show good agreement with experimental data and industrial experience. Abstract: Despite significant effort spent on the investigation of catalytic oxidation of ammonia on platinum at the molecular scale, there is surprisingly little work that investigates the behavior of the established reaction mechanisms under industrial conditions in the presence of mass transfer limitations. This paper presents reactive flow simulations of ammonia oxidation on platinum gauzes under industrial operating conditions, combining a mechanistic description of the surface chemistry with the computation of the flow-, temperature- and concentration fields around the platinum wires. Overall, the simulations yield temperature- and concentration fields, as well as integral N2 O selectivity in line with industrial experience and (limited available) experimental data. In particular, the simulations predict the experimentally observed decrease of the integral N2 O selectivity with increasing wire diameter, increasing wire-to-wire distance, decrasing flow velocity, and increased surface area due to surface reconstruction. The main result of the paper is that the local interaction of the flow field with surface chemistry leads to a variation in the local N2 O (and N2 ) selectivity across the gauze: The N2 O and N2 selectivity is higher on the front side of a wire than on the rear side. A reduced N2 O selectivity is observed where one wire is shadowed by another wire. Increased N2 O selectivity is observed at stagnation points where upstream wires direct the flow so that it hits a downstream wire with higher velocity. These examples show that - through the flow directing effect of the upstream wires - the selectivity on an individual wire is influenced by the presence of other wires. This observation provides a mechanistic explanation for the industrial observation that optimized gauze geometries can lead to reduced N2 O formation. Understanding the effect of local mass transfer on the selectivity provides a guideline for a further rational optimization of gauze geometries for improved N2 O and N2 selectivity. To analyze the robustness of the simulation results towards uncertainties in the reaction mechanism, a sensitivity analysis is performed, and the selectivity order defined as n S N 2 O, N H 3 = ∂ ln S N 2 O / ∂ ln c NH 3 (i.e. the response of the N2 O selectivity S N 2 O to changes in the near-wall NH3 concentration c N H 3 ) is identified as the decisive property of a reaction mechanism, that controls the response of the local selectivity to variations in the flow field. This suggests that future mechanistic work should focus on a more precise determination of this selectivity order n S N 2 O, N H 3 .